A tensionable suture-based cerclage is an alternative to stainless steel cerclage fixation for stabilization of a humeral osteotomy during shoulder arthroplasty - Denard, Patrick; Nolte, Philip-Christian; Millett, Peter J.; Adams, Christopher R.; Liebler, Stephenie A. H.; Rego, George; Higgins, Laurence D. (Journal of the American Academy of Orthopaedic Surgeons, 2021)
Introduction: - Fixation of periprosthetic humeral fractures is most commonly obtained with steel-based wires or cables; however, disadvantages with these constructs are numerous. Suture-based cerclages offer the advantage of easy handling, less radiographic interference, and risk of metallosis, as well as decreased risk of cutting into the soft humeral bone. Therefore, the purpose of this study was to compare a suture-based cerclage to a stainless steel wire cerclage (SSWC) for stabilization of the humerus during shoulder arthroplasty. - Methods: - In part I of the study, SSWC fixation was compared with single-looped tape cerclage and a double-looped tape cerclage (DLTC) fixation. In part II, a subsidence test was performed on 12 cadaveric humeri. After an osteotomy, the humeri were secured with either a SSWC or DLTC. Subsequently, a metal wedge was introduced into the humerus to simulate the stem of a shoulder arthroplasty. - Results: - In part I, load to 2-mm displacement was significantly higher for the DLTC construct compared with the SSWC construct (2,401 ± 483 N versus 750 ± 33 N; P < 0.0001). Load to failure was 935 ± 143 N with the SSWC, 1,737 ± 113 N with the single-looped tape cerclage, and 4,360 ± 463 N with the DLTC constructs, and all differences were statistically significant (P < 0.05). In part II, load at 20-mm subsidence was higher for the DLTC (320 ± 274 N) compared with the SSWC (247 ± 137 N), but no significant difference was observed (P > 0.05). However, gap displacement at 20 mm subsidence was significantly lower with the DLTC construct (0.33 ± 0.31 mm versus 0.77 ± 0.23 mm; P = 0.009). Load to failure was higher with the DLTC construct compared with the SSWC construct (4,447 ± 2,325 N versus 1,880 ± 1,089 N; P = 0.032), but the final gap displacement did not differ significantly (DLTC 5.23 ± 6.63 mm versus SSWC 6.03 ± 8.82 mm; P > 0.05). - Discussion: - A DLTC has higher load to failure and trends toward lower gap displacement compared with a SSWC. The DLTC construct may therefore be a viable alternative for fixation of periprosthetic fractures or osteotomies of the humeral shaft during shoulder arthroplasty.
Gesehen am 01.10.2021